STRATEGI GAME-BASED LEARNING BERBANTUAN MEDIA GENIALLY TERHADAP MOTIVASI BELAJAR MATEMATIKA MATERI BANGUN DATAR - Fauzan Sayyid Sahri; Husna Farhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Game-Based Learning strategy assisted by Genially interactive digital media on the mathematics learning motivation of second-grade students at SDN Bahagia 05 on the topic of plane figures. This research was motivated by the low mathematics learning motivation among lower-grade students, caused by the abstract nature of the material and the use of conventional teaching methods that were less engaging. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 60 students, namely 30 students of class IIA as the experimental group and 30 students of class IIC as the control group. Data on learning motivation were collected through a validated Likert-scale questionnaire and analyzed using the Independent Samples t-Test. The results showed a significance value of 0.019 (less than 0.05), so that H0 was rejected and H1 was accepted. The mean posttest score of the experimental group (63.63) was higher than that of the control group (58.97). Furthermore, the experimental group's motivation increased while the control group's decreased. Therefore, the Game-Based Learning strategy assisted by Genially has a positive effect on students' mathematics learning motivation.